1969
DOI: 10.1113/jphysiol.1969.sp008740
|View full text |Cite
|
Sign up to set email alerts
|

The significance of the shape of the lens and capsular energy changes in accommodation

Abstract: SUMMARY1. A method for the estimation of the energy released by the anterior part of the lens capsule during accommodation is described. This includes (i) A determination of the pressure required to distend the capsule by a standard volume.(ii) The calculation from the photographed lens profiles of the degree of capsular contraction which occurs when the lens changes from the unaccommodated to the accommodated form.(iii) Capsular volume changes in vitro are then related to the surface area changes calculated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
2

Year Published

1973
1973
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(60 citation statements)
references
References 8 publications
4
54
2
Order By: Relevance
“…It is known that with increasing age, age-related changes are seen in ciliary apparatus, zonular fibres, and lens capsule, lens elasticity decreases, lens thickness and stiffness increases, ability to disaccommodate decreases and ciliary muscle remodelling decreases independent of PEX. 3,[16][17][18][19][20] In our opinion, the reason why PEX did not affect accommodation amplitude in the second age group is that as age-related changes have already been happened in ciliary apparatus, zonular fibres and lens capsule in this age group, and the measured accommodation amplitude in this group is not active accommodation, and tonic accommodation is independent from lens elasticity, zonular fibres, and ciliary muscle. So, accommodation amplitude declined significantly only in group 1 in which active accommodation is still present with a small amount.…”
Section: Discussionmentioning
confidence: 97%
“…It is known that with increasing age, age-related changes are seen in ciliary apparatus, zonular fibres, and lens capsule, lens elasticity decreases, lens thickness and stiffness increases, ability to disaccommodate decreases and ciliary muscle remodelling decreases independent of PEX. 3,[16][17][18][19][20] In our opinion, the reason why PEX did not affect accommodation amplitude in the second age group is that as age-related changes have already been happened in ciliary apparatus, zonular fibres and lens capsule in this age group, and the measured accommodation amplitude in this group is not active accommodation, and tonic accommodation is independent from lens elasticity, zonular fibres, and ciliary muscle. So, accommodation amplitude declined significantly only in group 1 in which active accommodation is still present with a small amount.…”
Section: Discussionmentioning
confidence: 97%
“…Calculation of the change in dioptric power of the lens from the lens number and lens shape It has been shown that changes in the dioptric power of the lens, provided it changes from one ellipsoidal profile to another during accommodation, could be related to changes in the shape of the lens (Fisher, 1969b). From the previous paragraphs the change in shape of the lens is proportional to the lens number while the change in dioptric power is calculated from Appendix eqn.…”
Section: R F Fishermentioning
confidence: 99%
“…Calculation of relative capsular strain when differences of pressure within the lens are equalized In a previous paper Fisher (1969b) the concept of an equivalent spherical segment, representing the anterior portion of the lens, was employed to estimate the energy stored in the lens capsule. The change in radius (8Rm) of this theoretical sphere can in like manner be used to give a proportionate estimate of the capsular strain necessary to change pressure within the capsule.…”
Section: R F Fishermentioning
confidence: 99%
See 1 more Smart Citation
“…2 Presbyopia is the progressive loss of accommodation amplitude with age and appears to arise due to an alteration in the biomechanical coupling of the lens and its capsule. 3,4 The clinical presentation of presbyopia coincides with the massive sti®ening of the lens¯ber cells, but it is unclear whether this is purely correlation, cause, or e®ect. 5 While it remains unclear whether this relationship is causal or correlative, accurate measurement of lens' mechanical properties may give important insights into potential mechanisms of lens sti®ening and possibly presbyopia.…”
Section: Introductionmentioning
confidence: 99%